Perancangan dan Pengembangan Atopia Shop Platform E-Commerce untuk Fashion dan Aksesoris - Nur Ani Haryani; Layyi NatulMaisaroo; Alfalva Shelma Firoos Savero; Alvian Nur Romadhoni; David Ryan Wijaya; Hendri Noviyanto; Abdullah Zailani (Surakarta Abdimas Journal, 2025)
Abstract This community service aims to help Toko Atopia. this business started from home in Sambi, Boyolali, in facing the challenges of limited market reach and difficulties in the in-person shopping process. To overcome these problems, this community service focuses on creating an e-commerce website designed to make it easier for customers to shop online and expand Toko Atopia's market reach. With the launch of this website, it is expected to improve product accessibility, transaction efficiency, and customer shopping experience. This service method includes designing and developing an e-commerce website that includes a product catalog and important features to improve interaction with customers. In addition, the integration of WhatsApp services is designed to facilitate direct communication between customers and the store, allowing customers to ask for product information, place orders, and get help more easily.  Keywords : atopia store, e-commerce, website, online shop, marketing